Law's language : meaning and normativity / Daniel Wodak. - Wodak, Daniel (Cambridge elements. Elements in philosophy of law,, 2025)
The language of law includes normative or prescriptive terms such as 'obligation' and 'permission'. How do we explain the meaning of prescriptive legal language? This has long been regarded as a problem for positivists, since at first glance their view suggests we can derive an ought - a legal obligation or right or permission - from descriptive social facts alone. This Element outlines what we should want from a semantics of prescriptive legal language, critically evaluates four leading semantic accounts, and argues that legal prescriptivity is not, in the end, a problem for positivists.